A morphopragmatic study of [X-word] constructions through their morphological replicability and pragmatic functions - José Antonio Sánchez Fajardo (Lexis: Journal in English Lexicology)
The objective of this study is twofold. Firstly, it aims to examine the process of morphological replicability (MR) of [X-word] constructions (e.g. n-word, f-word, l-word) through the effects of the evaluative meaning of [X]- on the overall frequency of these constructions in the data. Employing a combination of the usage-based and the prototype approaches, this research study seeks to assess how dysphemistic constructions analogically extend out from prototypical euphemistic ones through MR. The second objective is to attempt at illustrating, from a pragmatic perspective, the variety of intentions behind the use of [X-word] constructions. The dataset, which is extracted from the NOW Corpus, includes a total of 24 [X-word] categories (e.g. a-word, b-word), the first 200 hits in each of which are examined to determine the meaning of [X]- and the pragmatic function associated with the construction, as well as to calculate the index (R), which is directly proportional to the MR rate. The index (R) is measured by dividing the total number of [X]- bases, or (f), by the total number of [X-word] constructions, or (F). The findings show that [X-word] constructions with a dysphemistic function (e.g. f-word